Catering for two hundred - Dow, Ula May (My University, 1905)
Introduction: During the last few years, it has been generally recognized that for the proper nourishment of the human body, it is necessary to feed what is known as a balanced dietary. It would seem to be difficult to put this into practice, but with very little experience one can determine from the class of foods used, whether, or not, a menu conforms to the dietary standard. A banquet usually means intemperance as far as quantity of food is concerned. Five or six courses as usually served give a calorie value nearly sufficient for an entire day. The effects of an unbalanced menu, therefore, are largely multiplied by the, quantity, thus making a careful consideration of the nutritive ratio necessary. Other elements to be considered in planning are cost, amount and order of preparation. The most practical method of estimating cost and amount is to take each separate food to be served and by actual experiment determine the amount and cost per capita. These could then be multiplied by the number of plates to be served. Taking for example, a brown bread sandwich to be served with a fish course, the process of gathering data is as follows: Once the given recipe is prepared and steamed in a can of suitable size and shape for use. The percentage of swelling in cooking is estimated and from this, the number of times the recipe needed to fill the can. This loaf is steamed, cooled and made into sandwiches. The data obtained from the experiment is then, 1. Amount of materials needed to make a definite sized loaf. 2. Number of sandwiches this loaf will make. 3. Amount of butter necessary to spread the sandwiches.
Citation: Dow, Ula May. Catering for two hundred. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Planning Meals; Pricing; Menus; Theses